2020
DOI: 10.1111/cas.14414
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of the inhibitors of RAF/MEK and AXL on KRAS‐mutated ovarian cancer cells with high AXL expression

Abstract: KRAS mutation is frequently seen in a subtype of ovarian cancer categorized as type 1. The KRAS‐MAPK pathway, which is closely involved in type 1 cancer progression, is under the regulation of receptor tyrosine kinases (RTKs). AXL, one of the RTKs, has been reported to be overexpressed in ovarian cancer and contributes to the poor prognosis. However, there is no useful target‐based agent against such gene profiles. We examined the combined effect of the dual RAF/MEK inhibitor CH5126766 and AXL inhibitor R428 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…It remains to be better determined what role AXL plays in necroptosis and PCD in NSCLC. 72 This is consistent with the observation by Zhang et al that the AXL immunohistochemistry pattern was heterogenous even in the acquired resistance settings, consistent with similar findings for other bypass track RTKs, such as the kinase MET. 47 In response to targeted therapeutics, how crosstalk between AXL and other activated RTKs gives rise to tumor heterogeneity is yet to be fully understood.…”
Section: Axl and Nsclc Therapy Resistancesupporting
confidence: 92%
See 1 more Smart Citation
“…It remains to be better determined what role AXL plays in necroptosis and PCD in NSCLC. 72 This is consistent with the observation by Zhang et al that the AXL immunohistochemistry pattern was heterogenous even in the acquired resistance settings, consistent with similar findings for other bypass track RTKs, such as the kinase MET. 47 In response to targeted therapeutics, how crosstalk between AXL and other activated RTKs gives rise to tumor heterogeneity is yet to be fully understood.…”
Section: Axl and Nsclc Therapy Resistancesupporting
confidence: 92%
“…Another study reported low AXL level as a predictive biomarker for therapy-induced necroptosis and programmed cell death (PCD) in cancers of diverse origin. 72 The authors found that the dual inhibition blocked both MAPK and PI3K/AKT cell signaling pathways and in result upregulated Bim, a potent molecule that initiates cellular apoptosis. It remains to be better determined what role AXL plays in necroptosis and PCD in NSCLC.…”
Section: Axl and Nsclc Therapy Resistancementioning
confidence: 99%
“…Currently, the ovarian cancer molecular markers routinely detected in clinical practice are cancer antigen 125 (CA125) ( 12 ), carcinoembryonic antigen (CEA) ( 13 ), human epididymis protein 4 (HE4) ( 14 ), carbohydrate antigen 19-9 (CA19-9) ( 15 ), mesothelin ( 16 ), α-fetoprotein ( 17 ), PARP ( 18 ), FRα ( 19 ), TP53 ( 20 ), HRD ( 21 ), BRCA1/2 ( 22 ) and AXL ( 23 ) ( Table I ); however, the detection of only one of these markers often provides an inaccurate result ( 24 ). CA125 is the most frequently used biomarker in the diagnosis of ovarian cancer ( 25 ), while HE4 was introduced as a biomarker more recently.…”
Section: Diagnosismentioning
confidence: 99%
“…A unique Raf/MEK inhibitor, VS-6766/CH5126766, has shown activity in xenograft models of RAS-mutated cancers [111,112]. In parallel, combined treatment with VS-6766/CH5126766 and AXL inhibitor (bemcentinib) has provided a stronger blockage of tumor growth in KRAS-mutant ovarian cancer cells with overexpressed AXL [113]. This allosteric inhibitor prevents the release of MEK from Raf, and thus blocks the subsequent phosphorylation of both MEK and Erk [114].…”
Section: Mek Inhibitorsmentioning
confidence: 99%